2021
DOI: 10.34172/jhp.2021.56
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, biological activities and toxic effects of alkaloidal constituents of genus Delphinium - A mini review

Abstract: The genus Delphinium is one of the essential members of the family Ranunculaceae. These species grow wild in North America, Europe, and Asia. They have demonstrated antioxidant, antimicrobial, and cytotoxic activities. Diterpenoid alkaloids are their main constituents and seem to be responsible for medicinal and toxic properties. The primary purpose of this paper is to review the therapeutic benefits of Delphinium species, chemical composition, and its medicinal uses, in addition to the reported toxic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…In this investigation, DPPH radical scavenging, Hydroxyl scavenging effect, reducing power, and superoxide radical anion scavenging have shown the antioxidant potential of D. roylei extracts and were observed to be significant when compared to positive controls such as Ascorbic acid, BHT, Rutin, and BHT respectively. These observations are in accordance with the previous studies on the antioxidant potential of Delphinium malabaricum extracts that the DPPH radical scavenging assay has investigated and the Ferric reducing antioxidant power (FRAP) assay ( Lotfaliani et al, 2021 )…”
Section: Discussionsupporting
confidence: 92%
“…In this investigation, DPPH radical scavenging, Hydroxyl scavenging effect, reducing power, and superoxide radical anion scavenging have shown the antioxidant potential of D. roylei extracts and were observed to be significant when compared to positive controls such as Ascorbic acid, BHT, Rutin, and BHT respectively. These observations are in accordance with the previous studies on the antioxidant potential of Delphinium malabaricum extracts that the DPPH radical scavenging assay has investigated and the Ferric reducing antioxidant power (FRAP) assay ( Lotfaliani et al, 2021 )…”
Section: Discussionsupporting
confidence: 92%
“…Among them, medicinal herbs, which comprise a quarter of all vascular plants in the flora of Kazakhstan, are a sought-after natural resource [18]. Hence, practical significance lies in the data related to the reserves of raw materials acquired for 18 officially recognized medicinal herbs that possess a variety of therapeutic effects, for Achillea millefolium (stomachic, antihelminthic) [19], Aconitum leucostomum (analgesic, antiarrhythmic) [20], Alhagi pseudalhagi (choleretic, hypolipidemic) [21], Cistanche salsa (antibacterial, for diseases of the reproductive and circulatory systems) [22,23], Delphinium elatum (emetic, diuretic) [24], Filipendula ulmaria (antiulcerogenic, hypoglycemic) [25], species Glycyrrhiza L. (expectorative, detoxification) [26], Hippophae rhamnoides (polyvitaminic) [27], Juniperus pseudosabina (antiseptic) [28], Origanum vulgare (expectorative, sedative) [29], Ziziphora clinopodioides (cardiotonic, general tonic) [30], Patrinia intermedia (sedative, hypotensive) [31], Hypericum perforatum (astringent, anti-inflammatory), Peganum harmala (anticholinesterase, abortive), Rheum tataricum (astringent, antineoplastic), Rumex tianschanicus (P-vitamin, laxative), Veratrum lobelianum (antineoplastic, antibacterial) [32].…”
Section: Resultsmentioning
confidence: 99%
“…‘Nirmasi’, or ‘Nirmashi’, one of the commonly used medicinal herbs in Nepal, is a species that belongs to the genus Delphinium of the family Ranunculaceae of which more than 356 species are identified. Nirmasi is infamously used for fever, headache, abdominal pain, jaundice, epilepsy, cough, and skin rashes which may be attributed to its antimicrobial, anti-inflammatory, antineoplastic, antifeedant, and cholinesterase inhibition properties 1 , 2 . As studies have suggested, the substance responsible for the medicinal properties of Delphinium is diterpenoid alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…As studies have suggested, the substance responsible for the medicinal properties of Delphinium is diterpenoid alkaloids. However, it is a lesser-known fact that the same substances have the potential to cause toxicity with manifestations ranging from gastric irritation to fatal arrhythmias 1 , 3 . We present a novel case of the occurrence of a ventricular storm after ingestion of Delphinium as an herbal treatment for their acidity.…”
Section: Introductionmentioning
confidence: 99%